The Role of Health Education in Improving Clean and Healthy Living Behavior (PHBS) in Rural Communities - Raharyani, Dessy (AMK : Abdi Masyarakat UIKA, 2025)
This study aimed to explore in-depth the community's understanding of infectious disease prevention through a qualitative approach, focusing on the level of health awareness, attitudes, and behaviors of people from different social, economic, and cultural backgrounds in urban and rural areas. Data were collected through in-depth interviews and focus group discussions (FGDs) involving participants from different walks of life to explore factors that influence preventive knowledge and practices, such as access to accurate health information, level of trust in formal health services, and cultural values and social norms prevailing in the community. The results revealed significant variations in the level of understanding and behavior of infectious disease prevention between community groups, with cultural and social factors often serving as both barriers and enablers to preventive action. The findings confirm the need for a community-based, contextual, and participatory health education approach, involving local leaders and interactive communication methods that suit the characteristics of the community, so that health promotion programs can be more effective, sustainable, and able to raise awareness while significantly changing community behavior in preventing the spread of infectious diseases.